Glycolysis reprogramming in cancer-associated fibroblasts promotes the growth of oral cancer through the lncRNA H19/miR-675-5p/PFKFB3 signaling pathway - Jin Yang; Xueke Shi; Miao Yang; Jingjing Luo; Qinghong Gao; Xiangjian Wang; Yang Wu; Yuan Tian; Fanglong Wu; Hongmei Zhou (Nature Publishing Group, 2021)
Abstract As an important component of the tumor microenvironment, cancer-associated fibroblasts (CAFs) secrete energy metabolites to supply energy for tumor progression. Abnormal regulation of long noncoding RNAs (lncRNAs) is thought to contribute to glucose metabolism, but the role of lncRNAs in glycolysis in oral CAFs has not been systematically examined. In the present study, by using RNA sequencing and bioinformatics analysis, we analyzed the lncRNA/mRNA profiles of normal fibroblasts (NFs) derived from normal tissues and CAFs derived from patients with oral squamous cell carcinoma (OSCC). LncRNA H19 was identified as a key lncRNA in oral CAFs and was synchronously upregulated in both oral cancer cell lines and CAFs. Using small interfering RNA (siRNA) strategies, we determined that lncRNA H19 knockdown affected proliferation, migration, and glycolysis in oral CAFs. We found that knockdown of lncRNA H19 by siRNA suppressed the MAPK signaling pathway, 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) and miR-675-5p. Furthermore, the lncRNA H19/miR-675-5p/PFKFB3 axis was involved in promoting the glycolysis pathway in oral CAFs, as demonstrated by a luciferase reporter system assay and treatment with a miRNA-specific inhibitor. Our study presents a new way to understand glucose metabolism in oral CAFs, theoretically providing a novel biomarker for OSCC molecular diagnosis and a new target for antitumor therapy.